(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
This study aimed to analyse the environmental quality based on opportunistic taxa and dominant taxa of macrobenthic assemblages, comparing sediment under the IMTA-aquaculture and the reference site, Karimunjawa National Park. Sediments were sampled between May and October 2019, in two sampling times at the IMTA cages in which star pomfret (Trachinotus blochii) and tiger grouper (Epinephelus fuscoguttatus) were farmed with 3 stations. The reference area was located 1 km away from the fish farm zone. Transformed data of macrobenthic abundance was correlated to abiotic variables using BIO-ENV using Primer V.6.1.5 software. The dominant taxa at IMTA sites were Diala semistriata, Rissoina ambigua, Stilifer ovoideus, Acteocina fusiformis, Cerithium punctatum, Allorchestes compressa and Capitella capitata, whilst those at the reference sites were dominated by Barbatia lima, Acteocina candei, Cerithium punctatum, Owenia fusiformis, and Anaspides spinulae. Further analyses on the selected dominant and opportunistic taxa of macrobenthic assemblages between the IMTA area (M = 10.18, SE = 2.056) and the reference area (M = 3.18, SE = 0.732) still showed a significant difference (t(42) = 3.207, p = 0.003), indicating a consistency of the results of parametric statistical tests, both using the complete and the selected data set. The use of selected and dominant taxa is effective in determining environmental status and level of disturbance, and speed up the identification process and monitoring time.